Prognostic significance of CD47 in human malignancies: a systematic review and meta-analysis - Zhao, Hui-Jun; Pa, Fei; Shi, Yi-Chao; Luo, Xi; Ren, Rong-Rong; Peng, Li-Hua; Yang, Yun-Sheng (Translational Cancer Research, 2018)
Background: High CD47 expression has been indicated to predict a poor prognosis in human malignancies. However, the prognostic significance remains inconsistent. Methods: Eligible studies were identified in PubMed, Embase, Web of Science, and the Cochrane Library prior to July, 2017. Relevant articles were screened for overall survival (OS), disease-free survival (DFS), event-free survival (EFS), progression-free survival (PFS), and clinicopathological data. Hazard ratios (HRs) and odds ratios (ORs) with 95% confidence intervals (CIs) were pooled using Stata v.14.0 and Revman v.5.3 software, respectively. We also investigated heterogeneity, sensitivity, and publication bias for OS. Results: This meta-analysis investigated the prognostic value of CD47 expression in 38 cohorts reported in 17 articles with 7,229 cancer patients. We found that CD47 overexpression correlated with shorter OS in cancer patients (pooled HR =1.49; 95% CI: 1.36–1.62, P